2017
DOI: 10.1186/s12890-017-0539-7
|View full text |Cite
|
Sign up to set email alerts
|

Implication of species change of Nontuberculous Mycobacteria during or after treatment

Abstract: BackgroundCo-existence or subsequent isolation of multiple nontuberculous mycobacteria (NTM) species in same patient has been reported. However, clinical significance of these observations is unclear. The aim of this study was to determine clinical implications of changes of NTM species during or after treatment in patients with NTM lung disease.MethodsPatients with NTM lung disease, who experienced changes of NTM species during treatment or within 2 years of treatment completion between January 1, 2009 and De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 19 publications
1
13
0
Order By: Relevance
“…They are vulnerable to continuous environmental exposure to NTM and are likely to eventually develop NTM lung disease with mixed infection. In addition, there is a possible structural (physical) basis for mixed infections, as species of NTM may differ across ectatic bronchi or nodules, as was speculated in a recent study (26). This phenomenon is in line with previous studies of MAC lung disease, which reported that patients with nodular bronchiectatic forms are repeatedly infected with multiple strains (16,20).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…They are vulnerable to continuous environmental exposure to NTM and are likely to eventually develop NTM lung disease with mixed infection. In addition, there is a possible structural (physical) basis for mixed infections, as species of NTM may differ across ectatic bronchi or nodules, as was speculated in a recent study (26). This phenomenon is in line with previous studies of MAC lung disease, which reported that patients with nodular bronchiectatic forms are repeatedly infected with multiple strains (16,20).…”
Section: Discussionsupporting
confidence: 83%
“…Similarly, in a study of M. abscessus lung disease in which nearly all (98%) of the study subjects had bronchiectasis and nodular opacities, the prevalence of coexistent or previous MAC infection was as high as 55% (22). In a recent study that evaluated the conversion of NTM species, which included 12 patients with conversion from MAC to MABC or vice versa, all patients had nodular bronchiectasis (26).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In this study, around 30% of the pulmonary NTM patients had ≥2 species identified. As clinical treatment data was not gathered in current study, we cannot tell if was related to clinical treatment as suggested by Lee et al [63] However, we found that age ≥ 65 years and COPD were significantly associated with multispecies isolation with OR of 1.7 and 2.2 respectively. Chronic inflammation and remodelling of airways in COPD may play a role in the increased susceptibility to NTM infection.…”
Section: Discussionmentioning
confidence: 52%
“…In patients receiving treatment for MAC-PD, single respiratory isolation of M. abscessus probably requires no therapy 17 . However, the change from MAC to M. abscessus is usually accompanied by symptomatic and radiographic worsening 24 . Unlike other studies, the present analysis revealed that coexistence of MK and another NTM may be associated with a lower risk of MK-PD and initial high-grade sputum AFS is a risk factor for MK-PD, supporting the hypothesis that quantitative organism load might determine the clinical relevance of NTM-PD 8,11,25 .…”
Section: Discussionmentioning
confidence: 99%